Kontekstualni dejavniki spodbujanja avtonomije učencev pri učiteljih osnovne in srednje šole - Košir, Katja; Kos Strašek, Tjaša (Revija za elementarno izobraževanje, 2015)
Contextual Factors of Teachers’ Support to Student Autonomy in Basic and in Secondary School. The main purpose of the present research was to examine some factors of teachers’ support to student autonomy in basic and secondary school: job characteristics, teachers’ involvement in preparing students for external assessment of knowledge, and school achievements in external assessment. Additionally, we examined teachers’ gender and educational level as factors of support to student autonomy. In the study 260 teachers (78.8% females) participated, among them 144 (55.4%) teachers in basic school and 116 (44.6%) teachers in secondary school. The results show that there is no relation between perceived autonomy at work and support to student autonomy. . Teachers that prepare their pupils for external assessment score lower on autonomy support. We found no differences in autonomy support with regard to school achievements in external evaluation. Female teachers exhibit a higher level of autonomy support.
Keywords: autonomy support; pupils; teachers; assessment; job characteristics